Analysis of Compound Activities in Cinchona Officinalis as Antiaging With a Computational Approach - Esti Mulatsari; esti Mumpuni (Universitas Muhammadiyah Malang, 2022)
Several studies on plants that have antiaging properties have been widely published. From these studies, research has not been carried out on compounds in cinchona plants that may provide efficacy as antiaging. Initially, cinchona is a plant that is famous for its antimalarial properties. But the use of cinchona as an antimalarial has now been reduced so research needs to be done to look for another potential of the cinchona plant. This study aims to conduct a computational approach of compounds derived from cinchona as an inhibitor of the elastase, hyaluronidase, collagenase, and tyrosinase enzymes with oleanolic acid, EGCG, and arbutin as comparative compounds. The method used in this study is molecular docking using YASARA, Marvinsketch, PLANTS, VMD, and statistic R software. From the research results, six (6) candidates of active compounds as elastase enzyme inhibitors, twenty one (21) candidates of the active compound as hyaluronidase enzyme inhibitors, four (4) candidates of the active compound as collagenase enzyme inhibitors, and four (4) candidates of the active compound as tyrosinase inhibitors. Two compounds have potential as antiaging, i.e chlorogenic acid and Cyanidol 3-rhamnoglucoside.